Feeling the Burn: Angry Brothers, Adamant Sister, and Affective Relations in the Song of Songs (1:5-6; 8:8-12) - Spencer, Franklin Scott (The catholic biblical quarterly, 2019)
This study aims to flesh out the tense affective relations in the Songs of Songs between the female protagonist and her hostile brothers (Song 1:5-6; 8:8-12). Based on close textual analysis informed by biblical anger prototypes, Aristotelian rhetoric, and modern theories of emotion focused on appraisal, metaphor, affective stylistics, and script performance, I propose that the young woman character constructed in the Song attributes her brothers' ire to their perceived social belittlement resulting from her independent pursuit of love beyond their control. Accordingly, this putative slighting ignites their "action tendency" to keep their little - and belittling - sister under wraps through forced vineyard labor under the scorching sun. Their scheme backfires, however, as she refuses to be "walled" up by her brothers to boost their emotional, social, and economic interests. With remarkable vitality in the face of vulnerability, she persists in flipping their script and affirming her own identity: "My vineyard, my very own, is for myself" (8:12).